Energy efficiency index by considering number of occupants: a study on the lecture rooms in a university building - Noor Ameera Zakaria; Mohammad Yusri Hassan; Hayati Abdullah; Md Pauzi Abdullah; Faridah Hussin; Siti Maherah Hussin; Nur Najihah Abu Bakar (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
The building sector is attributed to approximately 40% of the nation’s energy consumption and this accounts for a significant percentage of the nation’s energy consumption. For this reason, energy efficiency in buildings has now become an important subject in the national energy scenario. Energy Efficiency Index (EEI) is one of the energy consumption indicators that is widely used in the building sector for measuring energy performance. This index is generally measured based on the energy used per unit of building floor area. However, this index is not able to directly identify other factors affecting energy usage. This paper suggests an Energy Efficiency Index (EEI) for determining the performance of lecturer rooms in a university building. Unlike the conventional EEI, the proposed EEI determines the room’s energy usage performance by considering the number of occupants. The study was conducted at the Faculty of Electrical Engineering, Universiti Teknologi Malaysia (UTM) and the results show that the number of occupants significantly influences the energy usage performance of rooms in a university building.